Eastern Baltic cod in distress: biological changes and challenges for stock assessment. (8th June 2015) - Eero, Margit; Hjelm, Joakim; Behrens, Jane; Buchmann, Kurt; Cardinale, Massimiliano; Casini, Michele; Gasyukov, Pavel; Holmgren, Noél; Horbowy, Jan; Hüssy, Karin; Kirkegaard, Eskild; Kornilovs, Georgs; et al.
Abstract: The eastern Baltic (EB) cod ( Gadus morhua ) stock was depleted and overexploited for decades until the mid-2000s, when fishing mortality rapidly declined and biomass started to increase, as shown by stock assessments. These positive developments were partly assigned to effective management measures, and the EB cod was considered one of the most successful stock recoveries in recent times. In contrast to this optimistic view, the analytical stock assessment failed in 2014, leaving the present stock status unclear. Deteriorated quality of some basic input data for stock assessment in combination with changes in environmental and ecological conditions has led to an unusual situation for cod in the Baltic Sea, which poses new challenges for stock assessment and management advice. A number of adverse developments such as low nutritional condition and disappearance of larger individuals indicate that the stock is in distress. In this study, we (i) summarize the knowledge of recent changes in cod biology and ecosystem conditions, (ii) describe the subsequent challenges for stock assessment, and (iii) highlight the key questions where answers are urgently needed to understand the present stock status and provide scientifically solid support for cod management in the Baltic Sea.